2022
DOI: 10.2478/jeb-2022-0021
|View full text |Cite
|
Sign up to set email alerts
|

Does Digitalization Widen Income Inequality? A Comparative Assessment for Advanced and Developing Economies

Abstract: The paper raises two questions: (1) Does digitalization contribute to wealth and income inequality? (2) Does it affect inequality differently between advanced and developing economies? For the answers, the paper investigates the impact of digitalization on inequality for a balanced panel dataset of advanced economies and a balanced panel dataset of developing economies from 2002 through 2020. It applies the system-GMM and PMG estimators for estimation and robustness check. Some exciting results it provides. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…The results of this study also confirm prior findings that digitalization can impact the labor markets in a major way since it changes current jobs and creates new ones that did not exist a few years ago (Mantulenko et al, 2021). Claims that the higher inclusion of women and rural communities thanks to digitalization (Nguyen, 2022;Zhang et al, 2023) means that more people participate in the workforce and contribute to a nation's productivity. Thus, the higher the level of digital skills of a population, the more likely it is to experience a higher value of labor productivity.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results of this study also confirm prior findings that digitalization can impact the labor markets in a major way since it changes current jobs and creates new ones that did not exist a few years ago (Mantulenko et al, 2021). Claims that the higher inclusion of women and rural communities thanks to digitalization (Nguyen, 2022;Zhang et al, 2023) means that more people participate in the workforce and contribute to a nation's productivity. Thus, the higher the level of digital skills of a population, the more likely it is to experience a higher value of labor productivity.…”
Section: Discussionsupporting
confidence: 86%
“…This is because digital skills offer the opportunity to increase the employment rates of women, minimize long-term unemployment, and widen the employment choices in terms of human and social capital for rural workers (Stofkova et al, 2022;Zhang et al, 2023). Yet, this may be different in various contexts as it has been demonstrated that digitalization can narrow inequalities in developed economies and widen this gap in developing economies (Nguyen, 2022).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…According to their findings, a 1% increase in robot density in 2005-2017 increased the Gini coefficient by 4.2%, while ICT did not affect inequality. Nguyen (2022) applied the GMM and PMG estimators for developed and developing countries for the period 2002-2020. According to the author's findings, while digitalization narrows inequality in developed economies, it widens it in developing economies.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…Researchers suggest that digitalization can improve economic activities, boost productivity, and offer low-cost financial tools for low-income individuals. Furthermore, digitalization is expected to enhance the skills of workers and create new opportunities for knowledge acquisition (Nguyen, 2022;Nguyen, 2023). In particular, digital financialization provides affordable credit facilities and financial instruments in rural areas, which can help close the income gap and reduce income inequality (Yao and Ma, 2022).…”
Section: Introductionmentioning
confidence: 99%